Konsep Habitus Bourdieu dan Budaya Populer dalam Cerpen Filosofi Kopi karya Dewi Lestari: The Bourdieu’s Habitus Conceptand Popular Cultural in Filosofi Kopi Short Story by Dewi Lestari - Ummu Fatimah Ria Lestari (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Popular fiction used to the marginally fiction. It was considered disfunction and no has the social goals. So, it was useless. But now, that popular fiction becomes interesting and favourite thing on public literary. This research discusses about habitus and popular cultural of society in Filosofi Kopi short story that written by Dewi Lestari. The goal of this research is to analyze and to describe about habitus and popular cultural of society in Filosofi Kopi short story that written by Dewi Lestari. Habitus and popular cultural of society was researched on intrinsic and extrinsics unsures on that short story. Habitus concept of Bourdieu using for describe the society’s life styles on Filosofi Kopi, so it can influence literary distinction of society. This research uses qualitative methods. This research uses some steps, there consist of the collecting data, manage data, and analizing data. Data was collected by library research. On that short story, the researcher was found the life style of urban society and their popular cultural. The habitus of its writer draws in its setting, characters, and plot. Each character on that short story has their habitus. The forming of their habitus can we found on plot of short story.